2021
DOI: 10.7759/cureus.20206
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Injury: Conservative Versus Surgical Treatment

Abstract: The most frequent type of ligament injury is an anterior cruciate ligament (ACL). The mechanisms of an ACL injury are classified as direct contact, indirect contact, and non-contact. Physical examination for the assessment of the ACL is commonly used in routine care in the evaluation of the knee and is part of the diagnostic process. Due to the high degree of variability in their presentation and outcomes, treatment must be tailored according to factors such as patient demographics, the severity of the damage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Others [18] have suggested that the intercondylar fossa is a three-dimensional structure and that the reference de nition of the clock face is not accurate in terms of the location of the tunnel.Jin [19] suggested that the anteromedial bundle also has a role in controlling knee rotation, so positioning the femoral tunnel near the anteromedial bundle stop can restore the original anatomical position and isometricity of the ACL in ACL reconstruction, and this approach has been shown to achieve better clinical results in subsequent studies, but did not quantify the rotation. Another group of scholars [20] advocate the use of Bernard's four-frame table method for locating the centre of the femoral tunnel.Matthew D [21] studied the kinematic characteristics of the knee joint after ACL reconstruction with different anatomical positioning methods under the same loading conditions by performing ACL reconstruction in cadavers, and found that both the anteromedial technique and the femoral tunnel centrally positioned femoral tunnel resulted in anterior-posterior and rotational stability back to its original functional state. At the same time, the centrally positioned ACL placement further improved the rotational stability of the knee without loss of anterior-posterior stability compared to the centrally placed anteromedial bundle graft.…”
Section: Discussionmentioning
confidence: 99%
“…Others [18] have suggested that the intercondylar fossa is a three-dimensional structure and that the reference de nition of the clock face is not accurate in terms of the location of the tunnel.Jin [19] suggested that the anteromedial bundle also has a role in controlling knee rotation, so positioning the femoral tunnel near the anteromedial bundle stop can restore the original anatomical position and isometricity of the ACL in ACL reconstruction, and this approach has been shown to achieve better clinical results in subsequent studies, but did not quantify the rotation. Another group of scholars [20] advocate the use of Bernard's four-frame table method for locating the centre of the femoral tunnel.Matthew D [21] studied the kinematic characteristics of the knee joint after ACL reconstruction with different anatomical positioning methods under the same loading conditions by performing ACL reconstruction in cadavers, and found that both the anteromedial technique and the femoral tunnel centrally positioned femoral tunnel resulted in anterior-posterior and rotational stability back to its original functional state. At the same time, the centrally positioned ACL placement further improved the rotational stability of the knee without loss of anterior-posterior stability compared to the centrally placed anteromedial bundle graft.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) tears are one of the most common orthopaedic sports injuries, affecting an estimated 250,000 individuals yearly in the United States and Canada [9]. Though nonoperative management (e.g., NSAIDs, physiotherapy and bracing) can be utilized to help athletes regain function and mobility, surgical intervention is often required [56].…”
Section: Introductionmentioning
confidence: 99%
“…The basic function of the anterior cruciate ligament (ACL) is to limit excessive anterior displacement and valgus rotation of the tibia relative to that of the femur. ACL injuries are frequently observed (Gianotti et al, 2009) however, standards guiding the decision of whether to operate after an ACL injury have not been clearly de ned ( Monk et al, 2016, Krause et al, 2018, Rodriguez et al, 2021, and there are no evidence-based arguments to recommend that either conservative or surgical treatment provides better functional outcomes. Furthermore, knee laxity after ACL injury can be compensated for by muscle strengthening and neuromuscular proprioceptive exercises (Elbaz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%